"Ero infeliz, Leandro temerario" : la adhesión de Pedro Soto de Roja a una fabulación mítica - Gregorio Cabello Porras (Cuadernos de Investigación Filológica, 2013)
"Ero infeliz, Leandro temerario: la adhesión de Pedro Soto de Rojas a una fabulación mítica" attends how a baroque author uses the various aspects of a mythical argument. The myth of Leandro in Soto's Desengaño de amor en rimas should be tackled by a tropological reading -as a mythical fusion- within the lave poems which make up the first part of the rhymes. In the second part, once in the desengaño, the reading will hold an alegorical and moralizing nuance, as an example to the readers of the text.